Insights Into Chemosensory Proteins From Non-Model Insects: Advances and Perspectives in the Context of Pest Management - Lizana, Paula; Mutis, Ana; Quiroz, Andrés; Venthur, Herbert (Frontiers in Physiology, 2022)
Nowadays, insect chemosensation represents a key aspect of integrated pest management in the Anthropocene epoch. Olfaction-related proteins have been the focus of studies due to their function in vital processes, such ashost finding and reproduction behavior. Hence, most research has been based on the study of model insects, namely Drosophila melanogaster, Bombyx mori or Tribolium castaneum. Over the passage of time and the advance of new molecular techniques, insects considered non-models have been studied, contributing greatly to the knowledge of insect olfactory systems and enhanced pest control methods. In this review, a reference point for non-model insects is proposed and the concept of model and non-model insects is discussed. Likewise, it summarizes and discusses the progress and contribution in the olfaction field of both model and non-model insects considered pests in agriculture.